Does Work Motivation Moderate The Relationship Between Responsibility Accounting, Competence, and Managerial Performance? - Hidayah, Nurul (JIFA (Journal of Islamic Finance and Accounting), 2021)
This study aims to determine the effect of employee responsibility accounting and competence on managerial performance with motivation as a moderate variable. The research was conducted by taking a sample of 100 respondents. The sampling technique in this study used a purposive sampling technique. The data analysis technique used is linear regression. The results showed that responsibility accounting had a positive effect on managerial performance. employee competence has no effect on managerial performance. Work motivation does not reduce the relationship between responsible accounting and managerial performance. Work motivation can strengthen the relationship between employee competence and managerial performance. This study provides a theoretical contribution to the development of a new model using work motivation variables. This study also makes a practical contribution to identifying the motivation of each employee in detail. Keywords: Responsibility Accounting; Competence; Work Motivation; Managerial Performance